KEPASTIAN HUKUM TERHADAP TANAH DRUWE PURA MELALUI PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) - SARI, NI LUH ARININGSIH (GANEC SWARA, 2024)
The aim of this research is to find out more clearly and in depth about legal certainty regarding Druwe Pura land through complete systematic land registration (PTSL). This research is a type of normative legal research (doctrinal legal research). Article 19 of the Basic Agrarian Law states that in order to ensure legal certainty that the Government will carry out land registration throughout the territory of the Republic of Indonesia, the National Land Agency as the implementer of duties in the agrarian sector in Indonesia is obliged to serve the needs of the people who wish to register their land. To implement the order contained in Article 19, Government Regulation Number 24 of 1997 concerning Land Registration was issued.  Parisada Hindu Dharma Indonesia (PHDI) has made a Memorandum of Understanding with the National Land Agency (BPN) Number: 189/PH.PHDI.Pusat/V/2023; Number: 20/SKB-HK.03.01/V/2023 concerning Implementation of Land Registration, Assistance for Prevention and Handling of Land Asset Problems under the auspices of Parisada Hindu Dharma Indonesia.  The implementation of this Memorandum of Understanding is further regulated in the Cooperation Agreement between Parisada Hindu Dharma Indonesia and the National Land Agency (BPN), with Number: 269/PH.PHDI.Pusat/II/2024; Number: 4/SKB-100. HK.03.01/II/2024.. Registration of land belonging to the Temple (Pura druwe land) as a place of worship through Complete Systematic Land Registration (PTSL)